Web-Based Planning of Geographic Information System Mapping of Broken Roads in Kampar Regency - Jamil Rasyid; Novi Yona Sidratul Munti; Deddy Gusman (Journal of Engineering Science and Technology Management, 2021)
Road is a land transportation infrastructure and transportation route that is very vital at this time. Damage to the road is a big problem for some people who use the road every day. Kampar Regency during 2020 damaged roads including high, lightly damaged asphalt surface conditions 59.20 km, gravel heavily damaged along 4.00 km, and heavily damaged dirt road surface conditions along 2.80 km. Damage to roads in Kampar Regency can cause various kinds of losses, such as obstruction of road access to the destination, accidents, and damage to vehicles due to passing through bumpy and potholed roads, thereby increasing vehicle repair operational costs. Damage to roads can be overcome by making plans in a web of public complaints to the authorities in reporting the location of damaged roads. The purpose of this research is to help make it easier for the public when reporting damaged roads to PUPR by using the online damaged road reporting system by entering their name and email. The research method used in this research is the waterfall method. This waterfall method has a sequential flow of software starting from planning. The design of this system uses the Unified Modeling Language (UML) and Object-Oriented Analysis Design (OOAD).